(untitled) (قضايا سياسية, 2022)
The water reality in Iraq indicates a real water crisis caused by internal issues related to poor investment in the water field and misuse of water، and external related to the control of neighboring countries over the sources of water resources and controlling the amount of water in an unfair manner and does not take the interests of other countries except according to their interests.